Lockdown lessons in health economics: The case of alcohol - Christopher Snowdon (Institute of Economic Affairs (IEA), 2022)
According to a popular theory in public health, limiting the availability, affordability and advertising of alcohol reduces per capita consumption of alcohol which, in turn, leads to a decline in alcohol-related deaths. The theory assumes that a decline in average consumption will lead to a reduction in heavy drinking. In the words of two proponents of the theory: 'to help the minority the "normal" majority must change'. Empirical evidence for this theory is mixed and conflicting. Nevertheless, it is used to justify government intervention in the alcohol market through policies such as advertising bans, licensing restrictions and higher taxes aimed at lowering per capita consumption. The first year of the COVID-19 pandemic in the UK provided a 'natural experiment' in which the impact of dramatic changes in the availability and marketing of alcohol can be examined. During two periods of lockdown lasting a total of five months, the number of alcohol outlets fell by approximately two-thirds and expenditure on alcohol advertising fell by approximately half. There was little change in the price of alcohol although it became slightly less affordable due to a fall in incomes. Per capita alcohol consumption fell by six per cent during the first lockdown and by four per cent in 2020 overall. There was, however, significant variance in the distribution, with heavy drinkers tending to drink more and moderate drinkers tending to drink the same or less. Despite the decline in per capita consumption, the UK saw a sharp rise in the number of alcohol-specific deaths of 18.7 per cent. It is plausible that restrictions on the availability of alcohol contributed to the decline in per capita consumption. Whatever the cause, the fall in consumption was not accompanied by a decline in either heavy drinking or in alcohol-related mortality, contrary to the public health model. The UK's natural experiment of 2020 provides further evidence that harmful drinking is not driven primarily, if at all, by 'commercial determinants' but by personal circumstances, hardship and stress. Policies based on the whole population approach should be abandoned, not just because they place costs on all drinkers but because they are a distraction from constructive policies that could help the minority who are at greatest risk.
Keywords: 330; Lockdown; Coronavirus; Alcohol consumption; Health economics; Great Britain; Lockdown; Coronavirus; Alkoholkonsum; Gesundheitsökonomik; Großbritannien